2007
DOI: 10.5195/jyd.2007.359
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Adulthood: Theory, Assessment and Application

Abstract: The later attainment of traditional adult roles by today’s youth compared to their counterparts of earlier decades has garnered considerable scholarly and public attention. This article describes a recent concept related to the transition to adulthood, known as emerging adulthood, including a discussion of relevant theory and historical background research. We then introduce a measurement instrument, the Inventory of the Dimensions of Emerging Adulthood (IDEA), which assesses identification with transition-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
305
6
21

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 227 publications
(370 citation statements)
references
References 15 publications
18
305
6
21
Order By: Relevance
“…During the scale development an additional dimension, other-focus, was created. In the first validation study of the IDEA, Reifman, Arnett and Colwell (2007) found that when comparing age groups, the IDEA sub-scales for identity exploration (i.e., trying Other-focus, exhibited the reverse pattern. The authors also found that across studies individuals in the emerging adulthood sample scored higher on identity exploration, other-focus, self-focus, and feeling "in-between" than did younger respondents (sixth through twelfth graders).…”
Section: Palabras Clave: Edad Adulta Emergente Jóvenes En Riesgo Anmentioning
confidence: 99%
See 1 more Smart Citation
“…During the scale development an additional dimension, other-focus, was created. In the first validation study of the IDEA, Reifman, Arnett and Colwell (2007) found that when comparing age groups, the IDEA sub-scales for identity exploration (i.e., trying Other-focus, exhibited the reverse pattern. The authors also found that across studies individuals in the emerging adulthood sample scored higher on identity exploration, other-focus, self-focus, and feeling "in-between" than did younger respondents (sixth through twelfth graders).…”
Section: Palabras Clave: Edad Adulta Emergente Jóvenes En Riesgo Anmentioning
confidence: 99%
“…The steepest slope was found in Class 2, these individuals increased linearly in emerging adulthood across the time points. Emerging adulthood is expected to increase from 18, peak, and then decline until approximately age 25 when adulthood is reached (Arnett, 2004;Reifman et al, 2007 (Sussman, 2010) and this might explain why the largest group is not characterized by steep growth.…”
Section: Latent Class Growth Curve Modelmentioning
confidence: 99%
“…Because this was the first effort to empirically identify progressive structural change in both the content and structure of the subjective meaning and significance of the life course experiences of emerging adults, the theoretical coders drew their conceptualization on the earlier reports of Arnett's qualitative research and the emerging literature on the IDEA (Reifman, Arnett, & Colwell, 2007). As can be seen from Figure 1, the conceptual model provided preliminary confirmatory evidence that the subjective meaning and significance of the experiences of emerging adults maps onto a developmental progression consistent with previous theoretical conceptualizations as well preliminary findings that begin to expand our empirical map of not only the structure and organization of emerging adults' sense of identity but the complex structural and organization changes involved as they undergo developmental change.…”
Section: Theoretical Analysis Task 1: Identifying Theoretical Categoriesmentioning
confidence: 99%
“…The Identity Dimensions of Emerging Adulthood-Qualitative Extension (IDEA-QE) builds on the pioneering worth of Reifman, Arnett, and Colwell (2007) in the development of the Identity Dimensions of Emerging Adulthood (IDEA) and the literature on emerging adulthood (e.g., Arnett's theory of emerging adulthood). The IDEA measures identification with emerging adulthood themes described by Arnett (2004;, including identity exploration, experimentation, negativity, other-focused, self-focused, and in-between using a Likert-like scale format.…”
Section: Measurementioning
confidence: 99%
See 1 more Smart Citation